Student Sport, Mass Sport and Sport of High Achievements - Kurbaniyazov Jannazar (Zien Journals, 2022)
The article reveals the meaning of the concept of "mass sport". It will focus on the differences and similarities of mass sports with high-performance sports, as well as the goals and objectives pursued by this current direction of the sports movement
Keywords: mass; sports; health; person